PENGARUH MODEL EXAMPLES NON EXAMPLES TERHADAP HASIL BELAJAR SISWA KELAS IV SD - Devia Ratna Sari; Tri Jalmo; Rini Rita T. Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2014)
This study aims to know the effect of examples non examples model towards students learning activities and students learning outcome. This study design was pretest-posttest non-equivalent group. Samples were IVa and IVb, chosen by saturated sampling. This research data is in the form of quantitative which analyzed by using U-test and the qualitative data which obtained form the observation sheet of learning activities and questionnaire responses of students were analyzed descriptively. The result of the research shows that the use examples non examples model can improve students' learning activity with the average score of each aspect in the experimental class was 90.22 with asking questions ability 97.83 as the highest aspect. While the average score of students' learning achievement in pretest was 41.73, posttest 79.95 and N-gain 0.60. All students' (100%) give positive responses that they were happy towards the use of examples non examples model. Therefore, it can be concluded that examples non examples model affected students' learning achievement significantly.Penelitian ini bertujuan untuk mengetahui pengaruh model examples non examples terhadap aktivitas belajar siswa dan hasil belajar. Desain penelitian pretes-postes kelompok non-equivalen. Sampel penelitian siswa kelas IVa dan IVb dipilih secara sampling jenuh. Data penelitian berupa data kuantitatif yang dianalisis menggunakan uji-U dan data kualitatif yang diperoleh dari lembar observasi aktivitas belajar dan angket tanggapan siswa yang dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa penggunaan model examples non examples dapat meningkatkan aktivitas belajar siswa dengan nilai rata-rata semua aspek pada kelas ekperimen 90,22 dengan aspek tertinggi kemampuan bertanya (97,83). Sedangkan hasil belajar siswa dengan rata-rata pretes pada kelas eksperimen 41,73, postes 79,95 dan N-gain 0,60. Semua siswa (100%) tanggapan positif yaitu senang terhadap penggunaan model examples non examples. Dengan demikian model examples non examples berpengaruh signifikan terhadap hasil belajar.Kata kunci : aktivitas belajar, examples non examples, hasil belajar